Building on the momentum: Sustaining telehealth beyond COVID-19. (May 2022) - Thomas, Emma E; Haydon, Helen M; Mehrotra, Ateev; Caffery, Liam J; Snoswell, Centaine L; Banbury, Annie; Smith, Anthony C
The 2019 coronavirus pandemic (COVID-19) has resulted in tremendous growth in telehealth services in Australia and around the world. The rapid uptake of telehealth has mainly been due to necessity – following social distancing requirements and the need to reduce the risk of transmission. Although telehealth has been available for many decades, the COVID-19 experience has resulted in heightened awareness of telehealth amongst health service providers, patients and society overall. With increased telehealth uptake in many jurisdictions during the pandemic, it is timely and important to consider what role telehealth will have post-pandemic. In this article, we highlight five key requirements for the long-term sustainability of telehealth. These include: (a) developing a skilled workforce; (b) empowering consumers; (c) reforming funding; (d) improving the digital ecosystems; and (e) integrating telehealth into routine care.